Hubert Lenoir et les révélations de l’affliction - Leguerrier, Louis-Thomas (Sens public, 2019)
Quand Hubert Lenoir, lors de son entrevue à Tout le monde en parle, a déclaré : « J’ai un peu le goût de me crisser en feu ces temps-ci », s’attirant les remontrances des animateurs qui jugeaient de mauvais goût le fait de dire une telle chose à la télévision, et de surcroît sur un plateau où se trouvait un invité ayant déjà fait une tentative de suicide, cela a provoqué un certain émoi dans le public, et on reprocha d’un côté au chanteur de banaliser le suicide et de l’autre aux animateurs d’avoir banalisé la détresse peut-être tout à fait sérieuse de celui-ci. Plutôt que de prendre part à ce débat, ou encore de proposer des stratégies pour briser les tabous au sujet du suicide, je voudrais aborder la dimension littéraire de ce fameux malaise télévisuel, qui est liée au malaise de l’époque contemporaine face à ce que j’appellerai ici la mise en scène de l’affliction.
Keywords: Hubert Lenoir; Susan Sontag; affliction; impudeur; indecency; literary; littéraire

“Saw You in the Dark”: Exploring Rufus Wainwright’s Emotional Vulnerability in Fan-Captured Live Performance Videos - Salerno, Stephanie (Performance Matters, 2019)

Serving Each Other: Sharing Economies and Affective Labour in Montréal's Kiki Scene - Tailor, Jesse (Université Carleton, 2019)
Against a tense socio-political backdrop of white supremacy, intensifying pressures of neoliberal fiscal austerity, and queer necropolitics, this thesis addresses performance-based activist forms of place-making for urban-based queer, trans, and gender nonconforming communities of colour. Using participant observation and qualitative interviews with pioneering members of Montréal’s Kiki scene and Ottawa’s emerging Waacking community and interpreting my findings through the theoretical lens of queer of colour theory, critical whiteness studies, queer Latinx performance studies and Chicana feminism, I argue that Kiki subculture, which is maintained by pedagogical processes of ‘each one, teach one’, is instrumental in facilitating i) life-affirming queer kinship bonds, (ii) alternative ways to simultaneously embody and celebrate nonnormative gender expression with Black, Asian, and Latinx identity, iii) non-capitalist economies of sharing, and iv) hopeful strategies of everyday community activism and resilience to appropriative processes during economic insecurity and necropolitical turmoil.